Immune checkpoint inhibitor therapy for malignant pleural mesothelioma. (December 2021) - Nowak, Anna K; Chin, Wee Loong; Keam, Synat; Cook, Alistair
Highlights: Checkpoint inhibitors in mesothelioma. Advances in predictive biomarker identification in mesothelioma. Biomarker discovery and treatment options in mesothelioma. Data science in mesothelioma. Abstract: Mesothelioma is a rare and universally fatal cancer linked to exposure to asbestos. Until recently, standard of care treatment was chemotherapy; a treatment resulting in a minimal survival extension, and not improved upon for almost twenty years. However, the advent of cancer immunotherapy – and in particular the immune checkpoint inhibitor class of drugs - has resulted in recently approved new treatment options, with more currently under investigation. Here, we review clinical trials of both single agent and combination checkpoint inhibitors in mesothelioma, plus studies investigating their combination with chemotherapy. We also describe current advances in biomarker identification regarding prediction of patient response to checkpoint inhibitors. Finally, we assess the probable future direction of the field; including where current and developing technologies are likely to lead – in terms of both biomarker discovery and treatment options.